Case study on One.99 shop. - Chan, Kwai Seng. (2008)
This paper is a case study based on the retail operations and consumer behaviour of One.99 Shop. Marketing implications are explored through secondary research, consumer surveys and in-store observations. It also included competitor analysis and future trends in the discount retailing industry.